PENGARUH SELF EFFICACY, PARTISIPASI ANGGARAN, PENEKANAN ANGGARAN, ASIMETRI INFORMASI TERHADAP BUDGETARY SLACK - Galuh Asri Pratiwi; Muslichah Muslichah (Value : Jurnal Manajemen dan Akuntansi, 2023)
Individual participation in the company's budgeting process can trigger the emergence of dysfunctional behavior in the form of the individual's tendency to commit budgetary slack.. The purpose of this research is to analyze the effect of self-efficacy, budgetary participation, budgetary emphasis, and information asymmetry on budgetary slack. This research adopts a quantitative approach, utilizing a survey methodology with a structured questionnaire. The analysis method includes descriptive statistics and assessments of data quality and multiple linear regression analysis. The study population and sample consist of 34 employees with structural positions involved in the budget preparation process at the Probolinggo Regency Disaster Management Agency. The findings reveal a negative correlation between self-efficacy and budgetary slack. Moreover, budget participation exhibits a positive influence on budgetary slack, along with budget emphasis. Additionally, information asymmetry is found to have a positive impact on the occurrence of budgetary slack. Keywords: Efficacy, Participation, Emphasis, Asymetric,  Slack